2017
DOI: 10.1186/s40168-017-0302-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pneumococcal conjugate vaccines on the temporal variation of pneumococcal carriage and the nasal microbiota in healthy infants: a longitudinal analysis of a case–control study

Abstract: BackgroundBacterial colonization of the upper airways is a prerequisite for subsequent invasive disease. With the introduction of the 7- and 13-valent pneumococcal conjugate vaccines (PCV7 and PCV13), changes in pneumococcal upper airway colonization have been described. It is, however, less evident whether the vaccines lead to compositional changes of the upper airway microbiota. Here, we performed a case–control study using samples from a longitudinal infant cohort from Switzerland. We compared pneumococcal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 56 publications
(79 reference statements)
0
32
2
Order By: Relevance
“…The DADA2 algorithm has been shown to produce a higher resolution of microbial populations when applied to 16S rRNA gene sequences than the popular clustering into OTUs implemented in the mothur or QIIME pipelines ( 35 ). The resulting SVs only contain one read per SV, making additional analysis steps, such as oligotyping, unnecessary ( 36 , 43 ). Even though DADA2 leads to a decrease in alpha-diversity, it does not lead to changes in the community structure, which makes the approach comparable to results produced by other clustering algorithms ( 35 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DADA2 algorithm has been shown to produce a higher resolution of microbial populations when applied to 16S rRNA gene sequences than the popular clustering into OTUs implemented in the mothur or QIIME pipelines ( 35 ). The resulting SVs only contain one read per SV, making additional analysis steps, such as oligotyping, unnecessary ( 36 , 43 ). Even though DADA2 leads to a decrease in alpha-diversity, it does not lead to changes in the community structure, which makes the approach comparable to results produced by other clustering algorithms ( 35 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…By preventing disease and colonization by a targeted agent, vaccines produce differences in microbiota composition in vaccine recipients. Use of the 13-valent pneumococcal conjugate vaccine, but not the 7-valent vaccine, has been associated with higher diversity and stability of the nasal microbiota in immunized infants (98). An earlier study of the 7-valent pneumococcal vaccine revealed a shift in the composition of the nasopharyngeal microbiota at 12 months but not at 24 months postimmunization (99).…”
Section: Effects Of Vaccines On the Host-microbiome Relationshipmentioning
confidence: 99%
“…Regardless, the replacement of VT pneumococci represents a disruption in nasopharyngeal microflora. Evidence for indirect effects associated with PCV on Haemophilus disease and carriage have been noted 8-12 and PCV vaccination in the very young (<12 months) has been shown to cause a more disordered nasopharyngeal microbiota 41,42 . We hypothesise that this niche disruption, in combination with the adaptation of S. pneumoniae to maintain its relative fitness in the face of selective pressures in response to PCV introduction (Red Queen dynamics), 43 impacted the interactions between pneumococci and other microbiota resident in the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%